Digital financial services for empowering women in agri-food value chains in the Indonesian region - Putri, Rumanintya Lisaria (National Research and Innovation Agency, Indonesia, 2023)
This study seeks to explore the potential of digital financial services (DFS) and platforms to better serve the specific needs of rural women in the agri-food value chain (AFVC) to advance their financial inclusion, economic participation and opportunity. Based on an extensive literature review, available evidence and macro analysis of national-level statistical data, the study describes gender relations, DFS and AFVC in Indonesia, as well as identifies challenges in promoting women’s empowerment and opportunities to be exploited by DFS initiatives. The research identified women’s limited access to financial, productive, and capacity-building resources and limited decisionmaking roles over AFVCs as key challenges. More importantly, the research highlights four key areas of opportunity to be exploited: the suitability of designing DFS initiatives through an ecosystem approach, with an emphasis on partnerships and cooperation with multilevel stakeholders, including cooperatives and women’s associations; the importance of tailored training and effective communication channels to reach women through DFS initiatives; the relevance of DFS that accompanies it to the human touch and local presence through female agents; and the importance of collecting and analyzing sex-disaggregated data associated with the triple nexus. Recommendations are then presented to guide institutions, financial service providers, international organizations and civil society to design and deliver a more gender-responsive DFS in future initiatives.